2017
DOI: 10.1007/s13203-017-0177-2
|View full text |Cite
|
Sign up to set email alerts
|

Carbonylation of glycerol with urea to glycerol carbonate over supported Zn catalysts

Abstract: Glycerol carbonylation with urea is a very feasible option to produce glycerol carbonate with a net result of CO 2 fixation through urea synthesis. The prerequisite of an efficient catalyst for this reaction is to possess both acid and basic sites together. Several acidic supports were screened for ZnO catalyst in this work and Zn/MCM-41 was found to exhibit the best activity and almost complete selectivity to glycerol carbonate (GC). Although, non-catalytic glycerol carbonylation resulted in GC formation but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…The activation energy (Ea) obtained from present work was 50.5 kJ.mol -1 . This value could be compared to Zn/MCM-41 catalyst which gave activation energy of 39.82 kJ.mol -1 [20]. The value of Ea here was also lower than that of polystyrene, chitosan and commercial silica which gave 142.9, 163 and 166.7 kJ.mol -1 , respectively [7].…”
Section: The Results Of Kinetic Modeling and Parameter Estimationmentioning
confidence: 77%
See 1 more Smart Citation
“…The activation energy (Ea) obtained from present work was 50.5 kJ.mol -1 . This value could be compared to Zn/MCM-41 catalyst which gave activation energy of 39.82 kJ.mol -1 [20]. The value of Ea here was also lower than that of polystyrene, chitosan and commercial silica which gave 142.9, 163 and 166.7 kJ.mol -1 , respectively [7].…”
Section: The Results Of Kinetic Modeling and Parameter Estimationmentioning
confidence: 77%
“…Further, by comparing amberlyst-15 with ZnBr2 containing ionic liquid to catalyze the same reaction, it was found that glycerol conversion could reach 52 to 65% within the temperature range of 393-413 K with a catalyst loading of 0.5% [10]. Kondawar et al [20] investigated the influence of temperature within a range of 393-433 K over Zn catalyst. It was found that glycerol conversion increased from 56 to 95%.…”
Section: The Influence Of Reaction Temperature (353-383 K)mentioning
confidence: 99%
“…anks to its high surface area of 692 m 2 g −1 , well-dispersed ZnO phase onto the mesoporous framework of MCM-41, and good balanced acid (which activates urea molecules, 0.020 mmol g −1 ) with basic sites (which activates the glycerol, 1.61 mmol g −1 ), 75% glycerol conversion and 98% selectivity of GC were determined. Similarly, immobilizing ZnO catalyst onto the different acid carriers (MCM-41, SBA-15, SiO 2 , Al 2 O 3 , ZrO 2 , and s-ZrO 2 ) (5% Zn/MCM-41, 83% GC yield at 140℃ in 5 h) [64], Zn-exchanged zeolites including Zn-MOR, Zn-ZSM-5, Zn-beta, and Zn-FAU (Zn-HY-3, 93% GC yield at 150℃ for 3 h) [65], activated red mud-supported Zn/Al oxide catalysts (50% Zn/Al-ARM, 58.1% GC yield at 140℃ within 5 h) were also reported for efficient transformation of glycerol and urea into GC with relative good yields. Zinc exchanged heteropoly tungstate (Zn x TPA) catalysts were successfully developed and evaluated for selective carbonylation of glycerol with urea to manufacture GC [66].…”
Section: Reaction With Zinc-based Catalyst As Depicted Inmentioning
confidence: 99%
“…Carbonylation of glycerol with ethylene carbonate in supercritical carbon dioxide (CO 2 ) in the presence of zeolites and Amberlyst A26 (OH − and HCO 3 − forms of ion exchange resins) resulted in a low percentage of glycerol conversion of <25% [14]. The preparation of GC using urea as the carbonyl source and catalyst with Lewis acid sites associated with sulfonate groups of the polystyrene matrix was shown to be a more feasible route [18,19], exhibiting GC molar yields of 61% to 85% based on glycerol. Yoo et al [16] reported that the use of heterogeneous mesoporous zinc sulfate as a catalyst for the glycerol-urea reaction exhibited a good molar yield of 86%.…”
Section: Introductionmentioning
confidence: 99%